The Trypanosoma brucei La protein is a candidate poly(U) shield that impacts spliced leader RNA maturation and tRNA intron removal - Foldynová-Trantírková, Silvie; Paris, Zdenek; Sturm, Nancy R; Campbell, David A; Lukes, Julius (International journal for parasitology, 2005)
By virtue of its preferential binding to poly(U) tails on small RNA precursors and nuclear localisation motif, the La protein has been implicated for a role in the stabilisation and nuclear retention of processing intermediates for a variety of small RNAs in eukaryotic cells. As the universal substrate for trans-splicing, the spliced leader RNA is transcribed as a precursor with just such a tail. La protein was targeted for selective knockdown by inducible RNA interference in Trypanosoma brucei. Of three RNA interference strategies employed, a p2T7-177 vector was the most effective in reducing both the La mRNA as well as the protein itself from induced cells. In the relative absence of La protein T. brucei cells were not viable, in contrast to La gene knockouts in yeast. A variety of potential small RNA substrates were examined under induction, including spliced leader RNA, spliced leader associated RNA, the U1, U2, U4, and U6 small nuclear RNAs, 5S ribosomal RNA, U3 small nucleolar RNA, and tRNATyr. None of these molecules showed significant variance in size or abundance in their mature forms, although a discrete subset of intermediates appear for spliced leader RNA and tRNATyr intron splicing under La depletion conditions. 5'-end methylation in the spliced leader RNA and U1 small nuclear RNA was unaffected. The immediate cause of lethality in T. brucei was not apparent, but may represent a cumulative effect of multiple defects including processing of spliced leader RNA, tRNATyr and other unidentified RNA substrates. This study indicates that La protein binding is not essential for maturation of the spliced leader RNA, but does not rule out the presence of an alternative processing pathway that could compensate for the absence of normally-associated La protein.
Keywords: RNA, Small Interfering; Genes, Protozoan; sestřih RNA; RNA, Small Nuclear; RNA Splicing; protozoální geny; Protozoan Proteins; Animals; RNA se sestřihovou vedoucí sekvencí; protozoální proteiny; RNA, Spliced Leader; malá interferující RNA; RNA malá jaderná; RNA transferová; RNA, Transfer; zvířata; Trypanosoma brucei brucei